Božična jama pri Novi Štifti (Gornji Grad) – primer antičnega jamskega svetišča - Češarek, Domen; Jamnik, Pavel (Studia mythologica Slavica, 2020)
This article presents the archaeological and ethnological research of the Božična jama Cave in Slovenia, Styria region, as a possible shrine of fertility. The archaeological finds from the cave indicate that the cave was used for cult purposes. The authors point out the artificially built circle in the middle of the cave and suggest that it was probably devoted to establishing a cosmic space suitable for ritual purposes. The archaeological finds indicate the symbolism of the Sun, phallus and solar deity which are usually connected with fertility. The Božična jama Cave is thus far the only archaeological site in Slovenia to be confirmed as a Late Antiquity archaeological cave site that can be assumed to be a ritual cave connected with fertility.